STRATEGI MENGATASI SISWA YANG TIDUR SELAMA PEMBELAJARAN - Abubakar, Sarwan; Aziziy, Yunia Nabila (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This study aims to reduce students sleeping habits during learning in class 8C SMP Negeri 3 Sampang through the Classroom Action Research (PTK) method using teh Kurt Lewin model. Conducted in the even semester of the 2023/2024 school year, the study involved 32 students with a focus on changes in sleep patterns and learning concentration. From the results, internal and external strategies proved effective, including efforts to motivate students about the negative impact of sleep deprivation on health and learning performance, as well as changing the classroom atmosphere and conducting learning outside the classroom. The data showed that the majority of students experienced disturbed sleep patterns and had good learning concentration. The implication of this study is the importance of maintaining good sleep patterns to improve students’ learning concentration and health, taking into account the impact of technology such as smartphone use.